Magnetic Nanomaterials for Hyperthermia-Based Therapy, Imaging, and Drug Delivery - Constantin Mihai Lucaciu (MDPI AG, 2024)
In recent years, nanomedicine has experienced remarkable advancements, due to the development of new nanomaterials with outstanding properties that have demonstrated significant advantages over traditional medicines [...]